Судьба бьет вслепую - Серова Марина Сергеевна (Русский бестселлер, 2018)
Экземпляры: ф.11 (20180906) / Инвентарный номер: 50382 / Цена: 93.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44